2017
DOI: 10.1021/acscentsci.7b00022
|View full text |Cite
|
Sign up to set email alerts
|

Second-Order Biomimicry: In Situ Oxidative Self-Processing Converts Copper(I)/Diamine Precursor into a Highly Active Aerobic Oxidation Catalyst

Abstract: A homogeneous Cu-based catalyst system consisting of [Cu(MeCN)4]PF6, N,N′-di-tert-butylethylenediamine (DBED), and p-(N,N-dimethylamino)pyridine (DMAP) mediates efficient aerobic oxidation of alcohols. Mechanistic study of this reaction shows that the catalyst undergoes an in situ oxidative self-processing step, resulting in conversion of DBED into a nitroxyl that serves as an efficient cocatalyst for aerobic alcohol oxidation. Insights into this behavior are gained from kinetic studies, which reveal an induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 73 publications
1
34
0
Order By: Relevance
“…Interestingly, the Cu/DBED catalyst system is selective for the oxidation of activated secondary over primary alcohols, which is in contrast with the Cu/TEMPO• catalyst system [2,96]. Initially they believed that their catalyst system acts as a type II Cu-based tyrosinase mimic, instead of GOase [96], but the groups of Stahl and Arndsten and co-workers used mechanistic studies to confirm the presence of a nitroxyl radical during the oxidation reaction [96,97]. They proposed that Cu/DBED-catalysed reactions involve both oxygenase-and oxidase-type reactivity.…”
Section: Alternative Co-catalysts In Cu/nitroxyl-catalysed Alcohol Oxmentioning
confidence: 99%
“…Interestingly, the Cu/DBED catalyst system is selective for the oxidation of activated secondary over primary alcohols, which is in contrast with the Cu/TEMPO• catalyst system [2,96]. Initially they believed that their catalyst system acts as a type II Cu-based tyrosinase mimic, instead of GOase [96], but the groups of Stahl and Arndsten and co-workers used mechanistic studies to confirm the presence of a nitroxyl radical during the oxidation reaction [96,97]. They proposed that Cu/DBED-catalysed reactions involve both oxygenase-and oxidase-type reactivity.…”
Section: Alternative Co-catalysts In Cu/nitroxyl-catalysed Alcohol Oxmentioning
confidence: 99%
“…Copper–oxygen species are well-known in the active center of many enzymes 15 and organic synthetic transformations 6,7 to perform diversified oxidation reactions toward phenol 8 , alcohol 9 , amine 10 , and even hydrocarbons 11 . In efforts to obtain fundamental chemical insights into their structures and reactivity, a number of important copper–oxygen complexes have been identified 1218 .…”
Section: Introductionmentioning
confidence: 99%
“…A mechanistic study suggested that the secondary amine DBED was oxidized to the corresponding N-oxide product to generate reaction intermediates similar to the ones formed in the Cu/TEMPO/bpy system, including the key Cu II /N-oxide/alkoxy adduct (species D in Figure 9). 107 These findings might trigger the development of oxidation protocols based on the in situ generation of these oxidants (i.e., N-oxides). Given the ubiquity of amines in catalysis, the implication of N-oxides in oxidative functionalizations might not be unusual.…”
Section: Bioinspired Cu-promoted Oxidation Of Substrates Using O2 (Ormentioning
confidence: 99%